Surgical Treatment of Of The Isolated Cleft PALATE - Ahmad, Iftikhar; Jan, Abdullah; Zaman, Javed; Shahabi, Isteraj; Zaman, Noor; Khan, Farida (Journal of Postgraduate Medical Institute, 2011)
Summary Data on the surgical treatment of isolated cleft palates in 92 cases at the department of ENT. Head and neck surgery, Hayat shaheed teaching Hospital, Peshawar is presented. The assessment and management in these cases is outlined, and the imporance of timely surgical interventions is emphasized. Of the 92 patients on whom primary operation were performed, the face, jaws and teeth was hardly influenced. Out of 92 patients who had been operated, 63 percent had normal, 10 percent acceptable and 27 percent defective speech. Of the 25 patients with unsatisfactory speech after primary operation on the palate, a favourable improvement in speech could be achieved in 4 cases by reoperation on the palate.